Perspectives on Transdermal Electroporation - Kevin Ita (Pharmaceutics, 2016)
Transdermal drug delivery offers several advantages, including avoidance of erratic absorption, absence of gastric irritation, painlessness, noninvasiveness, as well as improvement in patient compliance. With this mode of drug administration, there is no pre-systemic metabolism and it is possible to increase drug bioavailability and half-life. However, only a few molecules can be delivered across the skin in therapeutic quantities. This is because of the hindrance provided by the stratum corneum. Several techniques have been developed and used over the last few decades for transdermal drug delivery enhancement. These include sonophoresis, iontophoresis, microneedles, and electroporation. Electroporation, which refers to the temporary perturbation of the skin following the application of high voltage electric pulses, has been used to increase transcutaneous flux values by several research groups. In this review, transdermal electroporation is discussed and the use of the technique for percutaneous transport of low and high molecular weight compounds described. This review also examines our current knowledge regarding the mechanisms of electroporation and safety concerns arising from the use of this transdermal drug delivery technique. Safety considerations are especially important because electroporation utilizes high voltage pulses which may have deleterious effects in some cases.